Narrating Trauma in Literature: Sorha Sanjhharu - Pokharel, Badri Prasad; Majgayna, Rita (Tribhuvan University Journal, 2016)
The ten years of conflict that changed the political, economic, and cultural landscapes of our country. This period has been the topic of study for the researchers or scholars who want to bring out the facts about the people either involved in conflict from either side. Ordinary civilians did not notice things in depth when the insurgency was at climax and left the Nepali society in dilapidated the life of condition. Among many notable writers who penned about it, Govind Bartaman has depicted some vulnerable people who were undergoing with crippled life from both warring groups. Narrating their pangs he has forwarded the indelible horrendous memory in the form of trauma of these people who are still in the traumas. The atrocities being narrated in the book are very traumatic but the form of narrative has appeased the pains of the traumatized and an appeal to adjust with the perpetrators.